Dinamika Hubungan Sipil-Militer dan Opini Publik dalam Pembentukan Keputusan Kebijakan Pertahanan - Sarjito, Aris (ANTASENA: Governance and Innovation Journal, 2024)
Abstract. In democratic states, civil-military relations and public opinion significantly influence defense policy decisions. This research explores the mechanisms through which civilian leaders and military officials interact to formulate defense policies, and how public sentiment, shaped by traditional and social media, impacts these decisions. Using qualitative research methods, specifically secondary data analysis of case studies and scholarly literature, this study investigates three key areas: the impact of civil-military relations on defense policy, the role of public opinion and media influence, and the interaction between civil-military relations and public opinion. Findings indicate that military leaders' public statements and media coverage significantly shape public opinion, which pressures civilian leaders to adapt defense policies. The U.S. withdrawal from Afghanistan is a prime example where declining public support, influenced by media portrayals and military assessments, led to a strategic policy shift. This study concludes that understanding the interplay between civil-military relations and public opinion is crucial for effective and democratic defense policy-making. Keywords: civil-military relations, defense policy, democratic states, media influence, public opinion